Efficacy of gabapentin mouthwash in managing oral mucositis pain in patients undergoing chemotherapy: a prospective, randomised, double-blind, controlled clinical trial. Issue 1 (February 2020) - Ala, Shahram; Zamani, Neda; Akbari, Jafar; Salehifar, Ebrahim; Janbabai, Ghasem; Koulaeinejad, Neda
Background and aims: Gabapentin has been used for the management of radiotherapy and chemotherapy induced stomatitis in a number of studies. Due to lack of sufficient evidence, the present study was designed to evaluate the efficacy of gabapentin mouthwash in oral mucositis associated pain in patients undergoing cancer chemotherapy. Methods and results: This study was a prospective, randomised, double-blind, placebo-controlled trial. The patients were randomly divided into two groups receiving either the gabapentin or placebo mouthwash. Patients were advised to rinse their mouth with 7 ml of solution for 30 s three times a day and were visited 10 days after initiation of the trial. The intensity of pain and severity of oral mucositis were assessed. Thirty-one patients received gabapentin mouthwash while 27 patients received placebo. Both gabapentin and placebo mouthwashes had decreased the pain intensity almost equally and did not show a significant difference between the two groups (P = 0.73). Also both gabapentin and placebo had reduced and improved swallowing, inflammation and erythema. But there was no noticeable difference between groups (P > 0.05). Conclusions: These findings indicate that gabapentin mouthwash did not show a significant activity as a pain relieving agent in chemotherapy induced oral mucositis associated pain.